Percutaneous Radio-Guided Chemical Ablation with Absolute Ethanol of Cystic and Solid Lesions in Kinshasa Hospital Environments (Global Journal of Medical Research, 2024)
Introduction the main objective of the present study is to evaluate the therapeutic effectiveness and safety of percutaneous radio-guided chemical ablation with absolute ethanol 96 in the therapeutic management of cystic and solid lesions benign localization thyroid classified EU-TIRADS 2 parathyroid hepatic renal inguino-scrotal ovarian as well as osteoarticular Materials and Methods Eighty patients were included in the present study Ages ranged from six to seventy-five After ultrasound reassessment psychological preparation premedication and local anesthesia we perform a puncture-drainage of the lesion under strict ultrasound guidance with good visualization of the bevel followed by rinsing for certain lesions and injection of 96 ethanol The volume of ethanol injected was obtained by calculating 10 to 20 of the overall volume of the lesion We performed one to three sessions of Sclerotherapy on our patients particularly on D1-D4 and D7 We studied the effectiveness of sclerotherapy through the complete drying of the lesion the reduction of the lesion volume to more than 50 of the initial volume as well as the disappearance of the pain As for recidivism it was evaluated by the persistence of pain the persistence or reappearance of the cystic lesion with a residual volume estimated at more than 50 Results Out of eighty patients listed We recorded 46 2 men and 53 8 women with a sex ratio of 0 83 The age of the patients was between 6 -75 years with an average age of 43 5 17 5 years The youngest patient was 6 years old and the oldest 75 years old The 37-47 age groups were the most represented with 26 3 The majority of women were aged between 26-36 and 37-47 years respectively 27 5 of the entire workforce In addition 17 5 of men were aged between 48-58 years Nearly 55 of our patients consulted for cervical swelling on an anatomopathological level almost 64 of our patients had an inflammatory smear 42 5 of the lesions treated were of thyroid location and the number of alcohol sessions depended on the organ treated the content of the alcoholic lesion gender without forgetting the volume of the alcoholic mass Radiologically the success rate was 95 apart from one treatment failure in four patients who were asymptomatic No complications haemorrhagic or infectious has been encountered except for one case of hypoglycemic shock which was quickly corrected Conclusion Ethanol 96 is an effective liquid sclerosing agent treating benign cystic lesions thyroid EU-TIRADS2 parathyroid hepatic renal Bosniak Ia osteoarticular inguino-scrotal as well as ovarian Given the ease of obtaining ethanol in sub-Saharan hospital environments Kinshasa in particular the simplicity of the procedure the low morbidity rate and its effectiveness obliges us to recommend percutaneous ethanol sclerotherapy as a treatment of first choice instead of other complex percutaneous ablation techniques The average volume of ethanol used was 12 85 ml the largest volume of ethanol was 40 ml and the smallest volume was estimated at 2 ml The average volume of treated lesions was 106 12 ml the smallest lesion volume was 4 ml and the large volume was 814 ml
Keywords: percutaneous radio-guided; chemical ablation; absolute ethanol; cystic lésions; solid lesions